2001
DOI: 10.1046/j.1360-0443.2001.961575.x
|View full text |Cite
|
Sign up to set email alerts
|

A review of expectancy theory and alcohol consumption

Abstract: Research is reviewed on the association between alcohol outcome expectancies and consumption which has led many to argue that manipulating expectancies might be a route to manipulating consumption for problem prevention and treatment. Studies indirectly and directly evaluating this latter position are reviewed. Expectancies predicting treatment outcome: two studies have shown that the more positive expectancies held at treatment, the poorer is treatment outcome, but five other studies have failed to find this.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

49
606
2
23

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 719 publications
(701 citation statements)
references
References 103 publications
49
606
2
23
Order By: Relevance
“…Specifically, clinical research has demonstrated that the amount of alcohol consumed is reliably correlated with the degree to which individuals have positive over negative alcohol outcome expectancies (Jones et al, 2001). The current findings provide insight into the development of such an imbalance in the weighting of positive and negative experiences and a candidate neural mechanism underlying the neurocognitive and behavioral consequences of adolescent alcohol consumption that may contribute to an enhanced vulnerability for developing AUD in adulthood.…”
Section: Discussionmentioning
confidence: 64%
“…Specifically, clinical research has demonstrated that the amount of alcohol consumed is reliably correlated with the degree to which individuals have positive over negative alcohol outcome expectancies (Jones et al, 2001). The current findings provide insight into the development of such an imbalance in the weighting of positive and negative experiences and a candidate neural mechanism underlying the neurocognitive and behavioral consequences of adolescent alcohol consumption that may contribute to an enhanced vulnerability for developing AUD in adulthood.…”
Section: Discussionmentioning
confidence: 64%
“…They are also dependent on negative experiences, such as failures, which may 'tend to lower their goals, decrease their efforts, and lessen the intensity and effectiveness of their strategy search' (Locke 1996: 120;Moskowitz 2002). In a similar vein, expectancy theory states that our behaviour is dependent on the reinforcing effects that we expect from performing (Bandura 1977;Jones, Corbin, and Fromme 2001), i.e. it relates to experiences that we have made in the past.…”
Section: Unlearning Through the End: The Loss Of Goalmentioning
confidence: 99%
“…Alcohol-related expectancies, both positive and negative, are beliefs about the effects of drinking alcohol. A substantial literature documents the association between alcohol expectancies and drinking behavior across time (e.g., Goldman, Brown, & Christiansen, 1987;Jones, Corbin, & Fromme, 2001). …”
mentioning
confidence: 99%